Opinion flow in news stories addressed to different audiences: the public debate on the Chilean pension system - Pacheco Ibaceta, Catalina Javiera; González Arias, Cristian; Santander Molina, Pedro (Círculo de Lingüística Aplicada a la Comunicación, 2023)
Public opinion is largely constructed by the contribution of mass media when publishing relevant events and opinions of various social actors on contingency issues. Opinion is transmitted not only in the opinion genres, such as editorials and columns, but also in the news stories, which transmit the journalists points of view about the events, as well as the opinions of social actors who have access to public space either directly or through quotes. As a way of identifying the opinion orientation in a public debate depending on the audience to which it is addressed, we suggest characterizing the opinion flow in the news stories of two newspapers of the same company. ‘Opinion flow’ is used in the sense of all the points of view expressed over the same subject in journalistic texts. We selected the newspapers El Mercurio and Las Últimas Noticias, for, as they belong to the same company, El Mercurio S. A. P., they are addressed to different audiences: the first is addressed to an upper and upper middle class audience, and the latter to a lower and lower middle class audience. In order to define the subject, we chose the public debate produced by the questioning of the Chilean pension system. We, therefore, pose the question: which are the differences in the opinion flow presented in the news stories of two newspapers that are addressed to different audiences and belong to the same company regarding the public debate about the pension system? Thus, we study the opinion flow by means of a four-level analysis, i.e. coverage, voices, issues and types of framing of the opinion. The results show systematic differences in the opinion flow regarding the two different audiences in all four levels studied.
Keywords: public debate; framing; opinion flow; news stories